Prevalence of Genetic Diversity between Group A and Group B of Respiratory Syncytial Virus Isolated From Hospitalized Patients in a Teaching Hospital in Kuala Lumpur - Gunasagaran, Vinomarlini (2005)
Respiratory Syncytial virus (RSV) is one of the most important causes of lower viral respiratory tract infection resulting in hospital admission among infants and early childhood worldwide. The virus is a seasonal virus, with annual outbreaks occurring during the winter in temperate climates and during the rainy season in tropical climates. The main objective of this study was to determine the prevalence of RSV group A and B in the Klang Valley area by using Polymerase Chain Reaction (PCR) as a rapid and simultaneous detection of RSV. In this study, Polymerase Chain Reaction (PCR) method was used to detect the RSV and seminested PCR was used to subtype RSV into groups. This method is more sensitive and reliable compared to the current method used for detecting RSV which is by using direct immunofluorescence immunoassay. The detection and subtyping of RSV both used the amplification of F and the G genes of RSV. The primer from the F gene region was used as the antisense primer for both detecting and subtyping while primer from different parts of the G gene region were used as the sense primer for detecting and subtyping of RSV respectively. Random Amplified Polymorphic DNA (RAPD) technique was performed in this research to study the diversity of twenty RSV isolates. Four out of fifteen primers that were screened for reproducible band yielded clear multiple bands. According to the dendrograrn generated from the RAPDistance software program, RSV isolates were distinctly separated into their own groups based on the year of isolation. The percentage of similarity among these isolates ranged from 33% to 95% while the Nei and Li's genetic distance obtained ranged from 0.0333 to 0.471. The data obtained from this study only covers the Klang Valley area as all of the samples were collected from patients that were admitted in the pediatric ward of University Malaya Medical Center, Kuala Lumpur. All the samples were obtained fiom September 2002 until March 2004. The samples were collected from patients age ranging from one month to one year. Out of the twenty RSV samples obtained, thirteen of the RSV isolates were from the male patients and seven were from the female patients. The highest rate of infection occurred in the Malay community followed by the Chinese and the Indian. The chi-square test was done in order to determine whether the clinical data such as age, gender and the ethnicity was significant with the RSV infection. This study shows that, the age, gender and the ethnicity of the patients were not significant and therefore, no relationship could be observed between the demographic data and the RSV infection. From this study, RSV was successfully detected in 20 samples by PCR method. The F and G genes were amplified to detect and subtype RSV into groups A and B. The incidence of RSV A was much higher from September 2002 until March 2004 compared to the RSV B. Therefore, RSV A is prevalent in the Klang Valley area.